PERSEPSI MAHASISWA TERHADAP TUTORIAL ONLINE MATA KULIAH PENGELOLAAN WILAYAH PESISIR DAN LAUT (KASUS: PROGRAM MAGISTER MANAJEMEN PERIKANAN UNIVERSITAS TERBUKA) - Ernik Yuliana; Adi Winata (Jurnal Pendidikan Terbuka Dan Jarak Jauh, 2009)
This article is aimed at exploring students perception of online tutorial program. The population is all of MMP (Magister of Fisheries Management Program, Universitas Terbuka, Indonesia) students attending the Marine and Coastal Area Management online tutorial program at registration time of 2008.1 in Jakarta and Ternate. All population members are engaged as responden. Data were collected by survey method and analysed by Rank Spearman non-parametric statistic method. The findings indicated that the students age level in Jakarta was dominated by early-adults (47,6%), while in Ternate was in middle-adults (73,3%). The main background of all students is fisheries (85,7% in Jakarta and 73,3% in Ternate). The skill in using internet of the Jakarta students were mostly at the mid level (66,7%), while the Ternate students were mainly at entry level (46,7%). The ability in using the internet (X3) is significantly correlated with the students perception of the questions in online tutorial program (Y2) at ? = 0,1.